TINGKAT PROFESIONALITAS GURU DALAM PEMBELAJARAN EKONOMI DI SMAN 1 SOOKO MOJOKERTO - Yosia Dian Purnama Windrayadi (Jurnal Pendidikan Ekonomi, 2017)
Facing growing competition in the age of education right now, all partiesneed to equate the thinking and attitudes to promote improved qualityeducation. then as the author of I want to know how far the level ofprofessionalism of teachers in study refers to Permendiknas the year of 2007that already assigned. The author would like to know how the professional inlearning ranging from planning, implementation, and evaluation. Here theauthor took rumusah problems about the application of professional teachersin the planning, implementation and evaluation and then coupled with asupporting factor and the factor restricting teachers become professional.From the results that have been obtained through observation anddocumentation indicate that economics teacher at SMAN 1 Sooko still not besaid because of the four professional competence set forth in thisGovernment Department, second economics teacher This is not yet able tomeet all of them, like the relationship with a less harmonious society, andalso the relationship of fellow teachers who have not undertaken smoothly,then the results of the second study video recording the teacher hadn't meetthe hours of lessons on the set, and also still using learning methodsaccording to the learners tend to be boring, thus there are 6 factors thatsupport the success ofachieving professional teacher SMAN 1 Sooko i.e.factor the presence of expertise each teacher, community support, a factor ofdukngan colleagues as teachers, government intervention, the demands ofthe teachers ' code of ethics, and the last factor is the scrutiny of theDepartment of education. In addition there is a supporting factor there isdefinitely a factor that inhibits a teacher could become a professionalatSMAN 1 Sooko Mojokerto, factors such a barrier is the lack of fulfillmentof the hour lesson, there is a lack of social interaction, the relationship is notgood against fellow teachers, and also the use of inappropriate methods oflearning in students. This indicates that the economics teacher at SMAN 1Sooko from the four competenciesno one has perfectly fulfilled, since thereare many challenges from within and from outside the teacher, but werecommend that teachers must be better learn to understand the conditionsenvironment, and also the feedback from learners over what has beenpresented so these existing barrier factor can be reduced and economicsteacher at SMAN 1 Sooko growing professional, and this is also a reflectionfor authors in particular for increasingly encouraged as to how these fourcompetencies will be fulfilled properly if the author worked as educators.Stanford University was set upin order for educators that is really able tomeet the province's existing competencies, because teachers are professionalin produce with the fulfillment of the four competencies that already exist. DOI: https://dx.doi.org/10.17977/UM014v10i12017p046